Design of Electrospun Poly vinyl alcohol/Chitosan Scaffoldand Its Cellular Study - Biazar, Esmaeil; Zaeifi, Davood; Heidari Keshel, Saeed; Ojani, Sanaz; Hajiaghaee, Arefeh; Safarpour, Roya; Sheikholeslami, Mahkameh; Heidari, Banafsheh; Sadeghpour, Saba (Archives of Advances in Biosciences, 2015)
Poly vinyl alcohol/Chitosan nanofibrous mat were prepared by electrospinning method with suitable pore sizes as potential matrices for soft tissue engineering. The designed scaffolds by electrospinning method evaluated by differentanalyses such morphological, mechanical, and cellular analysis.Microscopic results showed diameters of poly vinyl alcohol/Chitosan nanofibers were approximately 150 nm. Mechanical investigations illustratedstress - strain curve of poly vinyl alcohol /chitosan mat indicate good flexibility with average strain and good percentage of yield stress. The cellular resultsrevealthat addition of chitosan to poly vinyl alcohol enhances viability and proliferationof fibroblast cells, which increases the biocompatibility of the scaffold. In fact, addition of a smallpercentage of chitosan to the poly vinyl alcoholproved to be a promising approach for designof a scaffold.